2018
DOI: 10.1038/s41420-018-0067-0
|View full text |Cite|
|
Sign up to set email alerts
|

Phenotypic screening identifies a new oxazolone inhibitor of necroptosis and neuroinflammation

Abstract: Necroptosis is a regulated form of necrosis, which may be critical in the pathogenesis of neurodegenerative diseases. Neuroinflammation, characterized by the activation of glial cells such as microglia, is closely linked with neurodegenerative pathways and constitutes a major mechanism of neural damage and disease progression. Importantly, inhibition of necroptosis results in disease improvement, unveiling an alternative approach for therapeutic intervention. In the present study, we screened a small library o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…The anti-necroptotic effects, however, may not be solely dependent on this target. These results are in line with our previous work, where we showed the sequestration of key necroptosis mediators, RIP1, RIP3, and p-MLKL, in the insoluble fraction in zVAD-fmk-treated BV2 cells, while Oxa12 abolished necrosome assembly and MLKL phosphorylation [ 22 ]. Moreover, Oxa12 strongly rescued zVAD-fmk-induced cell death, as observed by microscopy analysis of cell morphology [ 22 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The anti-necroptotic effects, however, may not be solely dependent on this target. These results are in line with our previous work, where we showed the sequestration of key necroptosis mediators, RIP1, RIP3, and p-MLKL, in the insoluble fraction in zVAD-fmk-treated BV2 cells, while Oxa12 abolished necrosome assembly and MLKL phosphorylation [ 22 ]. Moreover, Oxa12 strongly rescued zVAD-fmk-induced cell death, as observed by microscopy analysis of cell morphology [ 22 ].…”
Section: Resultssupporting
confidence: 93%
“…These results are in line with our previous work, where we showed the sequestration of key necroptosis mediators, RIP1, RIP3, and p-MLKL, in the insoluble fraction in zVAD-fmk-treated BV2 cells, while Oxa12 abolished necrosome assembly and MLKL phosphorylation [22]. Moreover, Oxa12 strongly rescued zVAD-fmk-induced cell death, as observed by microscopy analysis of cell morphology [22]. Furthermore, our previous in silico molecular docking calculations for Oxa12 inside the RIP1 kinase domain demonstrated that Oxa12 is occupying a region similar to the co-crystallized inhibitor, suggesting a similar interaction pattern and indicating that Oxa12 most likely targets RIP1 to some extent [22].…”
Section: Phenotypic Screening For Hit Selectionsupporting
confidence: 93%
See 2 more Smart Citations
“…Rats with cognitive impairment induced by severe acute pancreatitis show increased levels of RIPK3 and RIPK1, and berberine can partly treat this cognitive impairment through attenuation of neuronal necroptosis[ 47 ]. Oliveira et al[ 48 ] have found that Oxa12, a new oxazolone, can reduce TNF-α-induced necroptosis in mouse L929 fibrosarcoma cells and zVAD-fmk-induced necroptosis in murine BV2 microglial cells. They have confirmed that Oxa12 disturbs the phosphorylation of MLKL and formation of necrosome complexes, which provides a new insight into the treatment of other inflammatory diseases.…”
Section: Drug Threapy Targeting In Necroptosismentioning
confidence: 99%